2006
DOI: 10.1128/aac.50.2.709-712.2006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Macrolide-Resistant Mycoplasma pneumoniae

Abstract: Macrolide-resistant Mycoplasma pneumoniae (MR M. pneumoniae) has been isolated from clinical specimens in Japan since 2000. A comparative study was carried out to determine whether or not macrolides are effective in treating patients infected with MR M. pneumoniae. The clinical courses of 11 patients with MR M. pneumoniae infection (MR patients) treated with macrolides were compared with those of 26 patients with macrolide-susceptible M. pneumoniae infection (MS patients). The total febrile days and the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
125
1
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 19 publications
16
125
1
5
Order By: Relevance
“…Despite numerous reports of detection of macrolide-resistant M. pneumoniae from clinical specimens, there have been few studies on the clinical impact of resistant strains. Children infected with macrolide-resistant M. pneumoniae have a longer duration of fever after initiating macrolide therapy than those infected with a macrolidesensitive strain, and macrolide was more likely to change to another antimicrobial [8]. However, in the study by SUZUKI et al [8], patients infected with macrolide-resistant strains were more likely to receive erythromycin or clarithromycin than azithromycin.…”
mentioning
confidence: 97%
“…Despite numerous reports of detection of macrolide-resistant M. pneumoniae from clinical specimens, there have been few studies on the clinical impact of resistant strains. Children infected with macrolide-resistant M. pneumoniae have a longer duration of fever after initiating macrolide therapy than those infected with a macrolidesensitive strain, and macrolide was more likely to change to another antimicrobial [8]. However, in the study by SUZUKI et al [8], patients infected with macrolide-resistant strains were more likely to receive erythromycin or clarithromycin than azithromycin.…”
mentioning
confidence: 97%
“…The rate of macrolide resistance among M. pneumoniae infections ranges from 3 to 26z in Europe (9,15), from 63 to 97z in China (16)(17)(18)(19), and from 25 to 93z in Japan (20)(21)(22). The total number of febrile days and the number of febrile days during macrolide administration are greater in patients infected with MR M. pneumoniae than in patients infected with macrolide-sensitive (MS) M. pneumoniae (23). Therefore, it is important to understand the regional prevalence of MR M. pneumoniae infections to predict the duration of fever caused by M. pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that macrolide resistance in M. pneumoniae may have clinical significance in terms of diminished response to treatment with drugs in this class (2,12,13). In Japan, reports of macrolide-resistant M. pneumoniae were from limited areas, and there have been no large-scale epidemiological studies conducted throughout Japan.…”
mentioning
confidence: 99%